Rates of post-traumatic stress disorder in trauma-exposed children and adolescents: meta-analysis. (May 2014) - Alisic, Eva; Zalta, Alyson K.; van Wesel, Floryt; Larsen, Sadie E.; Hafstad, Gertrud S.; Hassanpour, Katayun; Smid, Geert E.
Abstract : Background: It is unclear how many children and adolescents develop post-traumatic stress disorder (PTSD) after trauma. Aims: To determine the incidence of PTSD in trauma-exposed children and adolescents as assessed with well-established diagnostic interviews and to examine potential moderators of the estimate. Method: A systematic literature search identified 72 peer-reviewed articles on 43 independent samples ( n = 3563). Samples consisting only of participants seeking or receiving mental health treatment were excluded. Main analyses involved pooled incidence estimates and meta-analyses of variance. Results: The overall rate of PTSD was 15.9% (95% CI 11.5–21.5), which varied according to the type of trauma and gender. Least at risk were boys exposed to non-interpersonal trauma (8.4%, 95% CI 4.7–14.5), whereas girls exposed to interpersonal trauma showed the highest rate (32.9%, 95% CI 19.8–49.3). No significant difference was found for the choice of assessment interview or the informant of the assessment. Conclusions: Research conducted with the best available assessment instruments shows that a significant minority of children and adolescents develop PTSD after trauma exposure, with those exposed to interpersonal trauma and girls at particular risk. The estimates provide a benchmark for DSM-5 and ICD-11.